Titanium-boron synergistic dynamically cross-linked polysiloxane material and its solvent-free preparation method

By constructing a dynamic cross-linked polysiloxane material with titanium boron synergy, a network of dynamic covalent bonds (B–O), Ti–O–Si bonds, and enhanced hydrogen bonds was built, solving the corrosion and biotoxicity problems of the PBS system. This achieved efficient energy dissipation and rapid hardening, making it suitable for industrial production.

CN123042318APending Publication Date: 2026-11-06XI AN PEAK XUANKAI NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611407499.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing polyborosiloxane (PBS) systems suffer from the risks of boric acid corrosivity to steel and concrete, biotoxicity, and high energy consumption in high-temperature preparation processes. Furthermore, the slow hydrolysis and condensation of titanate esters in humid environments leads to long preparation cycles, which limits their applications.

Method used

The polysiloxane material with titanium-boron synergistic dynamic crosslinking forms a dual dynamic crosslinking network through B–O dynamic covalent bonds, Ti–O–Si bonds, and enhanced hydrogen bonds. A solvent-free kneader one-step process is adopted, with step feeding and gradient temperature control strategies to avoid competitive reactions of crosslinking agents, thereby achieving efficient energy dissipation and rapid hardening of the material.

Benefits of technology

The material exhibits efficient energy dissipation at low strain, rapid hardening response at high strain, excellent adaptive mechanical behavior over a wide strain rate range, short preparation cycle, good safety and biocompatibility, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123042318A_ABST
    Figure CN123042318A_ABST
Patent Text Reader

Abstract

This invention discloses a titanium-boron synergistic dynamic crosslinked polysiloxane material and its solvent-free preparation method, belonging to the field of polymer materials technology. The material is prepared by a dynamic crosslinking reaction of hydroxyl-terminated polysiloxane, titanate crosslinking agent, and borate crosslinking agent, possessing a dual dynamic crosslinking network composed of B-O dynamic covalent bonds, Ti-O-Si bonds, and enhanced hydrogen bonds. In the preparation process, the hydroxyl-terminated polysiloxane is added to a kneader for vacuum dehydration, followed by the sequential addition of borate ester for boration to form B-O-Si bonds, and then the addition of titanate ester for titanation to form Ti-O-Si bonds and enhanced hydrogen bonds. Post-treatment removes byproducts to obtain the final product. This invention, through the synergistic construction of a dual dynamic crosslinking network by titanium and boron, increases the material's storage modulus by over 10 in the frequency range of 0.1~100Hz. 4 It has the advantages of wide strain rate adaptive mechanical response, wide temperature range damping performance and self-healing ability, and the preparation process is solvent-free and has a short cycle, making it suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, and more specifically, to a titanium-boron synergistic dynamic crosslinked polysiloxane material and its solvent-free preparation method. Background Technology

[0002] Shear-hardening gels (SGs) are a class of smart materials whose modulus or viscosity increases significantly with increasing external strain rate, and they have broad application prospects in fields such as impact protection, flexible sensing, and damping. The shear-hardening behavior of SSGs usually originates from the dynamic cross-linking mechanism in their molecular network. Under external force, the dynamic cross-linking points can undergo reversible breakage and recombination, thereby achieving energy dissipation and modulus response.

[0003] Currently, most common SSG materials are polyborosiloxane (PBS) systems, which form dynamic covalent bonds (BO) through crosslinking of boric acid and polydimethylsiloxane at high temperatures (typically 180-220°C), endowing the material with typical shear hardening properties. However, the PBS system has the following significant problems: boric acid is corrosive to steel and concrete, and the corrosion rate is accelerated at high temperatures; boric acid has clear biotoxicity, and can cause toxic reactions through ingestion or absorption through broken skin, posing health and safety risks; the preparation process requires high-temperature conditions of 180-220°C, resulting in high energy consumption and a narrow process window. These safety hazards severely limit the application of SSG in many fields.

[0004] To address the aforementioned shortcomings of the PBS system, researchers have begun exploring SSG materials based on non-boron systems. One report describes a polytitanium siloxane (PTS) shear-hardening gel, which constructs a Si-O-Ti hybrid network through the hydrolytic condensation of tetraisopropyl titanate (TTIP) and hydroxyl-terminated polysiloxane, and utilizes Ti... 4+ / Ti 3+ The mixed valence states modulate the electrostatic potential of hydroxyl groups, forming enhanced hydrogen bonds, thereby achieving significant shear hardening properties (modulus increase of approximately 2800 times). This system avoids the use of boron, offering advantages in terms of safety and biocompatibility.

[0005] However, this PTS system still has the following shortcomings: the dynamic reversibility of the Si-O-Ti covalent network in this system is weak, the dynamic crosslinking effect mainly relies on the hydrogen bonding mechanism, the energy dissipation efficiency under low strain conditions is limited, and the network stability and tunability of mechanical properties need to be further improved; the titanate in this system needs to be slowly hydrolyzed and condensed in a humid environment, and usually needs to be placed under normal temperature and humidity conditions for a long time to complete the curing, resulting in a long preparation cycle, which is not conducive to continuous industrial production. To address the above problems, we propose a titanium-boron synergistic dynamic crosslinked polysiloxane material and its solvent-free preparation method. Summary of the Invention

[0006] The purpose of this invention is to provide a titanium-boron synergistic dynamic crosslinked polysiloxane material and its solvent-free preparation method, so as to solve the problems mentioned in the background art.

[0007] To achieve the above objectives, the present invention provides the following technical solution: A titanium-boron synergistic dynamic crosslinked polysiloxane material is prepared by a dynamic crosslinking reaction from raw materials comprising the following components: (a) Hydroxyl-terminated polysiloxanes, with the general structural formula: HO–[Si(R)2–O] n –H, where R is independently selected from one or more of methyl, ethyl, propyl, and phenyl, and n is an integer from 10 to 1000; (b) A titanate crosslinking agent selected from titanate compounds having chelating ligands; (c) A borate ester crosslinking agent selected from one or more of tributyl borate, trimethyl borate, and trimethoxyboroxane; The material has a dual dynamic cross-linking network composed of B–O dynamic covalent bonds, Ti–O–Si bonds, and enhanced hydrogen bonds.

[0008] Preferably, the titanate crosslinking agent is bis(triethanolamine)diisopropoxytitanate.

[0009] Preferably, the number average molecular weight of the hydroxyl-terminated polysiloxane is 500~50000 g / mol.

[0010] Preferably, the molar ratio of silanol groups in the hydroxyl-terminated polysiloxane to titanium atoms in the titanate is (1.5~4):1; the amount of borate ester, calculated in terms of boron atoms, has a molar ratio of (0.005~0.05):1 with the silanol groups in the hydroxyl-terminated polysiloxane.

[0011] Preferably, the energy storage modulus of the material increases by 10³ to 10⁻¹⁰ in the frequency range of 0.1 to 100 Hz. 5 The shear hardening sensitivity index (RST) is 10 times higher than that of the previous year. 3 ~10 7 %; and at a shear rate of 0.05~2 s -1 The maximum stress increase within the range is 10 to 30 times.

[0012] A solvent-free method for preparing a titanium-boron synergistically dynamically crosslinked polysiloxane material includes the following steps: Step 1, Pretreatment: Add the hydroxyl-terminated polysiloxane to a kneader, heat to 90~120℃, and stir and dehydrate under vacuum for 0.5~2 hours; Step 2, Boration reaction: Under nitrogen protection, add borate ester crosslinking agent to kneader, heat to 110~140℃, and stir for 1~3 hours under vacuum of -0.08~-0.098 MPa to allow the borate ester to undergo a condensation reaction with the silanol groups of the terminal hydroxyl polysiloxane to form B–O–Si dynamic covalent bonds. Step 3, Titaniumization reaction: Cool the kneader to 90~120℃, add the titanate crosslinking agent in batches under nitrogen protection, control the vacuum degree to -0.04~-0.07 MPa, and stir the reaction for 2~5 hours; Step 4, Post-processing steps: After the reaction is complete, the temperature is raised to 120~140℃, and by-products and unreacted small molecules are removed under a vacuum of -0.095 MPa. The material is then cooled and discharged to obtain the titanium-boron synergistic dynamic cross-linked polysiloxane material.

[0013] Preferably, the vacuum conditions in step one are a vacuum degree of -0.09 to -0.098 MPa and a temperature of 100 to 110°C.

[0014] Preferably, the temperature of the borylation reaction in step two is 120~130℃, and the reaction time is 1~2 hours.

[0015] Preferably, in step three, the titanate crosslinking agent is added in 2 to 5 batches, with an interval of 10 to 20 minutes between each batch; the reaction temperature is 100 to 110°C, and the reaction time is 3 to 4 hours.

[0016] Preferably, the time for removing byproducts in step four is 15 to 30 minutes.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention constructs a dual dynamic crosslinking network by simultaneously introducing titanium and boron elements into the same polysiloxane system. This network features the synergistic effect of B-O dynamic covalent bonds, Ti-O-Si bonds, and enhanced hydrogen bonds. The two dynamic crosslinking mechanisms exhibit differentiated response characteristics at different strain rates, enabling the material to possess both efficient energy dissipation at low strain and rapid hardening response at high strain. Experiments show that the storage modulus of the material of this invention increases by approximately 11,600 times in the frequency range of 0.1~100 Hz, which is far superior to that of the pure titanium system (approximately 56 times) and the pure boron system (approximately 72 times). The shear hardening sensitivity index (RST) reaches 1.16 × 10⁻⁶. 6 %, and at shear rates of 0.05~2s - The maximum stress increase within the range is approximately 19.8 times, significantly better than the 4.3 times increase of the pure titanium system, achieving a leap in shear hardening performance and adaptive mechanical behavior over a wide strain rate range.

[0018] (2) The present invention adopts a solvent-free kneading machine one-step process. By step feeding and gradient temperature control strategy, the borylation reaction is completed first and then the titanate is introduced. This effectively avoids the competitive reaction between the two crosslinking agents, realizes the precise control of the network structure, and does not require organic solvents throughout the process. The reaction temperature is only 100~140℃ and the total reaction time is only 4~6 hours. Compared with the existing PTS system (room temperature and humidity curing for 48 hours), the preparation cycle is significantly shortened. The process is green and environmentally friendly and suitable for large-scale continuous industrial production.

[0019] (3) The material of the present invention has excellent comprehensive performance, with both wide temperature range damping performance and room temperature self-healing ability. The effective damping temperature range (tanδ>0.3) is -40℃~60℃, and the room temperature repair efficiency can reach more than 85%. At the same time, by adjusting parameters such as titanium / boron ratio, reaction temperature and time, the dynamic crosslinking density and shear hardening response strength of the material can be easily controlled to meet the customized needs of different application scenarios. In addition, the present invention uses borate ester to replace boric acid as boron source, which eliminates the corrosive and biotoxic risks of boric acid from the source, and has obvious advantages in terms of safety and biocompatibility. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the preparation method of the present invention. Detailed Implementation

[0021] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0022] Example: A titanium-boron synergistic dynamic crosslinked polysiloxane material is prepared by a dynamic crosslinking reaction from raw materials comprising the following components: (a) Hydroxyl-terminated polysiloxanes, with the general structural formula: HO–[Si(R)2–O] n –H, wherein R is independently selected from one or more of methyl, ethyl, propyl, and phenyl, and n is an integer from 10 to 1000; wherein the number-average molecular weight of the hydroxyl-terminated polysiloxane is 500 to 50000 g / mol.

[0023] (b) A titanate crosslinking agent selected from titanate compounds having chelating ligands; wherein the titanate crosslinking agent is bis(triethanolamine)diisopropoxytitanate.

[0024] (c) A borate ester crosslinking agent selected from one or more of tributyl borate, trimethyl borate, and trimethoxyboroxane; In the raw materials, the molar ratio of silanols in the hydroxyl-terminated polysiloxane to titanium atoms in the titanate is (1.5~4):1; the amount of borate ester, calculated in terms of boron atoms, has a molar ratio of (0.005~0.05):1 with the silanols in the hydroxyl-terminated polysiloxane.

[0025] The material possesses a dual dynamic crosslinking network composed of B–O dynamic covalent bonds, Ti–O–Si bonds, and enhanced hydrogen bonds. The storage modulus of the material increases by 10³ to 10⁻¹⁰ in the frequency range of 0.1–100 Hz. 5 The shear hardening sensitivity index (RST) is 10 times higher than that of the previous year. 3 ~10 7 %; and at a shear rate of 0.05~2 s -1 The maximum stress increase within the range is 10 to 30 times.

[0026] Please see Figure 1 A solvent-free method for preparing a titanium-boron synergistically dynamically crosslinked polysiloxane material includes the following steps: Step 1: Pretreatment: Add the hydroxyl-terminated polysiloxane to a kneader, heat to 90~120℃, and stir and dehydrate under vacuum conditions for 0.5~2 hours; the vacuum conditions are -0.09~-0.098 MPa and the temperature is 100~110℃.

[0027] Step 2, Boration reaction: Under nitrogen protection, add borate ester crosslinking agent to the kneader, heat to 110~140℃, and stir for 1~3 hours under vacuum of -0.08~-0.098 MPa to allow the borate ester to undergo a condensation reaction with the silanol groups of the terminal hydroxyl polysiloxane to form B–O–Si dynamic covalent bonds; the boration reaction temperature is 120~130℃, and the reaction time is 1~2 hours.

[0028] Step 3, Titaniumization reaction: Cool the kneader to 90~120℃, add the titanate crosslinking agent in batches under nitrogen protection, control the vacuum degree to -0.04~-0.07 MPa, and stir the reaction for 2~5 hours; add the titanate crosslinking agent in 2~5 batches, with an interval of 10~20 minutes between each batch; the reaction temperature is 100~110℃, and the reaction time is 3~4 hours.

[0029] Step 4, Post-processing: After the reaction is complete, the temperature is raised to 120~140℃, and by-products and unreacted small molecules are removed under a vacuum of -0.095 MPa. The material is then cooled and discharged to obtain the titanium-boron synergistic dynamic cross-linked polysiloxane material. The time for removing by-products in step 4 is 15~30 minutes.

[0030] Example 1 This embodiment provides a titanium-boron synergistic dynamic crosslinked polysiloxane material and its preparation method.

[0031] Raw materials: Hydroxyl-terminated polydimethylsiloxane (HPDMS), number average molecular weight Mn≈2000 g / mol, hydroxyl content approximately 1.0 mmol / g, 100 parts by weight; bis(triethanolamine) diisopropoxytitanate (titanium ester crosslinking agent), 2.0 parts by weight; tributyl borate (boron ester crosslinking agent), 0.8 parts by weight.

[0032] Preparation method: (1) Add 100 parts by weight of hydroxyl-terminated polydimethylsiloxane to a laboratory kneader, heat to 110°C, turn on stirring, vacuum to -0.095 MPa, and dehydrate for 1 hour; (2) Purge with nitrogen to atmospheric pressure, add 0.8 parts by mass of tributyl borate, heat to 125°C, and stir for 1.5 hours under vacuum of -0.095 MPa; (3) Cool the kneader to 105°C, and under nitrogen protection, add 2.0 parts by weight of bis(triethanolamine)diisopropoxytitanate in 3 batches (15 minutes apart between each batch), control the vacuum degree to -0.05 MPa, and stir the reaction for 4 hours. (4) After the reaction is complete, the temperature is raised to 130°C, and the gas is degassed for 20 minutes under a vacuum of -0.098 MPa. The temperature is then lowered to below 60°C before discharge.

[0033] The resulting product is a colorless to pale yellow transparent viscous elastomer.

[0034] Example 2 The difference between this embodiment and Example 1 is that the amount of tributyl borate is 1.2 parts by weight, and the amount of bis(triethanolamine)diisopropoxytitanate is 3.0 parts by weight.

[0035] The remaining raw materials, proportions, and preparation methods are the same as in Example 1.

[0036] The resulting product is a pale yellow transparent elastomer with a higher crosslinking density than that of Example 1.

[0037] Example 3 The difference between this embodiment and Example 1 is that the borate ester crosslinking agent is trimethoxyboronoxane, and the amount used, calculated in terms of boron atoms, is the same as the molar amount of boron atoms in tributyl borate in Example 1.

[0038] The remaining raw materials, proportions, and preparation methods are the same as in Example 1.

[0039] Example 4 The difference between this embodiment and Example 1 is that the number-average molecular weight of the hydroxyl-terminated polysiloxane is approximately 5000 g / mol.

[0040] The remaining raw materials, proportions, and preparation methods are the same as in Example 1.

[0041] Example 5 The difference between this embodiment and Example 1 is that the hydroxyl-terminated polysiloxane is selected as hydroxyl-terminated poly(methylphenyl)siloxane, wherein the molar ratio of methyl to phenyl is 3:1, and the number average molecular weight Mn≈3000 g / mol.

[0042] The remaining raw materials, proportions, and preparation methods are the same as in Example 1.

[0043] Example 6 The difference between this embodiment and embodiment 1 is that the temperature of the borylation reaction in step (2) is 130°C and the reaction time is 1 hour; the temperature of the titanylation reaction in step (3) is 110°C and the reaction time is 3 hours. The titanyl ester is added in two batches with an interval of 20 minutes between each batch.

[0044] The remaining raw materials, proportions, and preparation methods are the same as in Example 1.

[0045] Comparative Example 1 (pure polytitanium siloxane, boron-free) Raw materials: 100 parts by weight of hydroxyl-terminated polydimethylsiloxane (same as in Example 1), and 2.0 parts by weight of bis(triethanolamine)diisopropoxytitanate.

[0046] Preparation method: Hydroxyl-terminated polydimethylsiloxane was added to a kneader and dehydrated under vacuum at 110°C for 1 hour. Then, titanate was added in batches under nitrogen protection and reacted at 105°C and -0.05 MPa for 4 hours. The post-treatment was the same as in Example 1.

[0047] Comparative Example 2 (pure polyborosiloxane, titanium-free) Raw materials: 100 parts by weight of hydroxyl-terminated polydimethylsiloxane (same as in Example 1), and 1.5 parts by weight of tributyl borate.

[0048] Preparation method: Hydroxyl-terminated polydimethylsiloxane was added to a kneader and dehydrated under vacuum at 110°C for 1 hour. Then, tributyl borate was added and reacted at 125°C and -0.095 MPa for 3 hours. The post-treatment was the same as in Example 1.

[0049] Comparative Example 3 (Existing PTS system, cured at room temperature and humidity) Raw materials: 100 parts by weight of hydroxyl-terminated polydimethylsiloxane (same as in Example 1), 5.0 parts by weight of tetraisopropyl titanate (TTIP).

[0050] Preparation method: Hydroxyl-terminated polydimethylsiloxane and TTIP are mixed evenly at room temperature and placed under normal temperature and humidity conditions (temperature 25℃, relative humidity 60%) for 48 hours. After complete curing, it is tested.

[0051] Performance testing (a) Shear hardening property test Dynamic frequency scanning tests were performed on the samples of each embodiment and comparative example using a rotational rheometer. The test conditions were: 25℃, strain 1%, and frequency range 0.1~100 Hz.

[0052] The shear hardening sensitivity index (RST) is used to quantify the shear hardening response intensity of a material, defined as: RST = (G′) / (G′) 100 Hz - G′ 0.1 Hz) / G′ 0.1 Hz × 100%. The relationship between the storage modulus of each embodiment and comparative sample and frequency is shown in Table 1.

[0053] Table 1 Storage modulus of different samples Note: RST (Shear Hardening Sensitivity Index) = (G′) 100Hz - G′ 0.1Hz ) / G′ 0.1Hz × 100%.

[0054] As shown in Table 1, the modulus improvement factors of Examples 1-6 are significantly better than those of Comparative Example 1 (pure titanium system) and Comparative Example 2 (pure boron system), demonstrating the synergistic effect of titanium and boron. Among them, Example 1, with a titanate content of 2.0 wt% and a tributyl borate content of 0.8 wt%, achieved excellent shear hardening properties, with the storage modulus increasing by approximately 11,600 times in the frequency range of 0.1-100 Hz.

[0055] Further analysis of the data in Table 1 shows that the RST value of Comparative Example 1 (pure titanium system) is 5.61 × 10³, and the RST value of Comparative Example 2 (pure boron system) is 7.20 × 10³, while the RST value of Example 1 is approximately 207 times and 161 times higher, respectively. These results indicate that the synergistic introduction of titanium and boron is not a simple superposition of two single systems, but rather a significant improvement in shear hardening performance achieved through the synergistic effect of B–O dynamic covalent bonds, Ti–O–Si bonds, and enhanced hydrogen bonds.

[0056] Compared with Comparative Example 3 (existing PTS system), the modulus of Example 1 increased by a factor of 1.16 × 10⁻⁶. 4 The ratio is approximately 4 times that of Comparative Example 3 (2.86 × 10³), indicating that the titanium-boron synergistic network of the present invention has a superior shear hardening response capability compared to the existing single titanium system.

[0057] (ii) Strain rate dependent mechanical response The stress-strain curves of the samples in each embodiment all exhibited a clear strain rate dependence. Taking Example 1 as an example, the stress response at different shear rates is shown in Table 2.

[0058] Table 2 Maximum stress at different shear rates in Example 1 As shown in Table 2, as the shear rate increases from 0.05 s⁻¹... - ¹Increased to 2 s - ¹, the maximum stress in Example 1 increased from 1.28 kPa to 25.30 kPa, an increase of approximately 19.8 times. The stress response instantaneously increased with increasing shear rate, indicating that the material has typical shear hardening characteristics, and its hardening response rate and magnitude are superior to those of existing single systems.

[0059] Comparative Example 1 (pure titanium system) under the same shear rate range (0.05~2 s⁻¹) - Within Example 1), the maximum stress increased from 0.82 kPa to 4.36 kPa, an increase of approximately 4.3 times, significantly lower than in Example 1. This result indicates that the titanium-boron synergistic network can form physical crosslinking points more rapidly under high strain rates, thereby achieving a more efficient hardening response.

[0060] (III) Comparison of preparation efficiency The preparation method of Comparative Example 3 requires 48 hours of curing under normal temperature and humidity conditions, which is a relatively long process. In contrast, the preparation method of Example 1 of this invention involves a solvent-free reaction in a kneader, with a total reaction time of approximately 6.5 hours (including 1 hour of dehydration, 1.5 hours of borylation, and 4 hours of titaniumization), which significantly shortens the preparation cycle and is suitable for large-scale continuous industrial production.

[0061] (iv) Damping performance test Damping performance of each sample was tested using a dynamic thermomechanical analyzer under the following conditions: temperature range -80℃ to 100℃, heating rate 3℃ / min, and frequency 1 Hz.

[0062] The peak loss factor (tan δ) of Example 1 is about 1.2, and the effective damping temperature range (tan δ>0.3) is -40℃ to 60℃, which is significantly wider than that of Comparative Example 1 (-20℃ to 40℃) and Comparative Example 2 (-30℃ to 50℃), indicating that the titanium boron synergistic network endows the material with better wide-temperature damping performance.

[0063] (v) Self-healing performance test The sample from Example 1 was cut into two segments, and the fracture surfaces were tightly fitted together at room temperature. After standing for 24 hours, the repair efficiency was tested. Based on tensile strength, the repair efficiency reached over 85%, indicating that the reversible breakage and recombination of the B–O dynamic covalent bonds endowed the material with excellent self-healing ability. In contrast, the repair efficiency of Comparative Example 1 (pure titanium system) under the same conditions was only 30%–40%.

[0064] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A titanium-boron synergistically dynamically crosslinked polysiloxane material, characterized in that, The raw materials comprising the following components are prepared by a dynamic cross-linking reaction: (a) Hydroxyl-terminated polysiloxanes, with the general structural formula: HO–[Si(R)2–O] n –H, where R is independently selected from one or more of methyl, ethyl, propyl, and phenyl, and n is an integer from 10 to 1000; (b) A titanate crosslinking agent selected from titanate compounds having chelating ligands; (c) A borate ester crosslinking agent selected from one or more of tributyl borate, trimethyl borate, and trimethoxyboroxane; The material has a dual dynamic crosslinking network composed of B–O dynamic covalent bonds, Ti–O–Si bonds, and enhanced hydrogen bonds.

2. The titanium-boron synergistic dynamic crosslinked polysiloxane material according to claim 1, characterized in that, The titanate crosslinking agent is bis(triethanolamine)diisopropoxytitanate.

3. The titanium-boron synergistic dynamic crosslinked polysiloxane material according to claim 1, characterized in that, The number-average molecular weight of the terminal hydroxyl polysiloxane is 500~50000 g / mol.

4. The titanium-boron synergistic dynamic crosslinked polysiloxane material according to claim 1, characterized in that, In the raw materials, the molar ratio of silanol atoms in the hydroxyl-terminated polysiloxane to titanium atoms in the titanate is (1.5~4):1; the amount of borate ester used, calculated in terms of boron atoms, has a molar ratio of (0.005~0.05):1 with the silanol atoms in the hydroxyl-terminated polysiloxane.

5. The titanium-boron synergistic dynamic crosslinked polysiloxane material according to claim 1, characterized in that, The energy storage modulus of the material increases by 10³ to 10⁻¹⁰ in the frequency range of 0.1 to 100 Hz. 5 The shear hardening sensitivity index (RST) is 10 times higher than that of the standard shear hardening index. 3 ~10 7 %; and at a shear rate of 0.05~2 s -1 The maximum stress increase within the range is 10 to 30 times.

6. A solvent-free preparation method of a titanium-boron synergistically dynamically crosslinked polysiloxane material as described in any one of claims 1-5, characterized in that, Includes the following steps: Step 1, Pretreatment: Add the hydroxyl-terminated polysiloxane to a kneader, heat to 90~120℃, and stir and dehydrate under vacuum for 0.5~2 hours; Step 2, Boration reaction: Under nitrogen protection, add borate ester crosslinking agent to kneader, heat to 110~140℃, and stir for 1~3 hours under vacuum of -0.08~-0.098 MPa to allow the borate ester to undergo a condensation reaction with the silanol groups of the terminal hydroxyl polysiloxane to form B–O–Si dynamic covalent bonds. Step 3, Titaniumization reaction: Cool the kneader to 90~120℃, add the titanate crosslinking agent in batches under nitrogen protection, control the vacuum degree to -0.04~-0.07 MPa, and stir the reaction for 2~5 hours; Step 4, Post-processing steps: After the reaction is completed, the temperature is raised to 120~140℃, and by-products and unreacted small molecules are removed under a vacuum of -0.095 MPa. The material is then cooled and discharged to obtain the titanium-boron synergistic dynamic cross-linked polysiloxane material.

7. The solvent-free preparation method of a titanium-boron synergistically dynamically crosslinked polysiloxane material according to claim 6, characterized in that, The vacuum conditions described in step one are a vacuum degree of -0.09 to -0.098 MPa and a temperature of 100 to 110℃.

8. The solvent-free preparation method of a titanium-boron synergistically dynamically crosslinked polysiloxane material according to claim 6, characterized in that, The borylation reaction in step two is carried out at a temperature of 120-130°C for 1-2 hours.

9. The solvent-free preparation method of a titanium-boron synergistically dynamically crosslinked polysiloxane material according to claim 6, characterized in that, In step three, the titanate crosslinking agent is added in 2 to 5 batches, with an interval of 10 to 20 minutes between each batch; the reaction temperature is 100 to 110°C, and the reaction time is 3 to 4 hours.

10. A solvent-free preparation method for a titanium-boron synergistically dynamically crosslinked polysiloxane material according to claim 6, characterized in that, The removal of byproducts in step four takes 15 to 30 minutes.